Pemuridan Digital: Menelusuri Peran Guru Pendidikan Agama Kristen sebagai Pemimpin Spiritual di Era Disrupsi Teknologi - Topayung, Semuel Linggi (JURNAL LUXNOS, 2025)
The rapid development of technology has changed the landscape of Christian religious education, introducing new challenges to the role of Christian Religious Education  teachers as spiritual leaders. This study aims to explore the role of PAK teachers in assuming spiritual responsibilities in the evolving digital age. Adopting a qualitative approach and literature review method, this study investigated how PAK teachers face and respond to technological developments in the context of Christian religious learning. Data analysis highlighted key challenges faced by PAK teachers, such as the negative influence of social media and students' lack of interest in Christian religious education, as well as the strategies they use to fulfill their role as spiritual leaders. The findings show that PAK teachers take innovative approaches, including the utilization of technology as a tool to enhance spiritual learning, building deep relationships with students, and strengthening parental and church community involvement. The implication of this study is the importance of increased support for PAK teachers in facing spiritual challenges in the digital age, as well as the importance of developing learning strategies that are relevant to the evolving technological context. This research makes an important contribution to the understanding of the role of PAK teachers as spiritual leaders in the midst of ever-changing technological developments